Double the bounty [large type] - Randisi, Robert J. (Wheeler Publishing large print western, 2010)
He almost paid the ultimate price for a crime he didn't commit. Now Decker is determined to track down others wanted by the law. He'll make sure the innocent have nothing to fear. But the guilty won't stand a chance against the bounty hunter. Brian Foxx was a legend. According to numerous eyewitnesses, he'd held up a bank in Wyoming and one in Arizona--on the exact same day at the exact same time. Decker has no idea how Foxx pulled it off, but he's got a legend of his own to maintain: no matter how wily the opponent or impossible the crime, Decker always gets his man.